SOSIALISASI K3 KELISTRIKAN RUMAH TANGGA DAN UPAYA PENGHEMATAN ENERGI DI DESA KULURAN KECAMATAN KALITENGAH KABUPATEN LAMONGAN - Zainal Abidin; Affan Bachri; Arief Budi Laksono (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
Socialization and counseling k3 and effort in saving energy to the village community is so public got insight and knowledge of security and safety work ( k3 ) in care and maintenance installation houses and make maximum savings in. electrical power consumptionSocialization the very enthusiastic in the event discussion and particular case k3, electricity a video and several efforts energy savings can be done in the community.